Performance based optimum seismic design of reinforced concrete structures. - Fragiadakis, Michalis
A fully atuomated design methodology based on nonlinear response history analysis is proposed for the optimum seismic design of reinforced concrete (RC) structures. The conventional trial and error process is replaced by a structural optimization algorithm that serves as a search engine capable of locating the most efficient design in terms of cost and performance. Two variations of the proposed design methodology are introduced. The first approach treats the optimum design problem in a deterministic manner, while in the second variation the optimum design is sought in the framework of a reliability based optimization problem. The reliability based approach seems to be a more rational procedure since more meaningful design criteria that correlate better with the performance based design concept can be adopted. Thus, the practice of using the mean annual frequency of a limit state being exceeded to assess the candidate structural response for a number of limit states, from serviceability to collapse prevention. The proposed design procedure is specifically tailored to the design of RC structures, where a preliminary design step of generating tables of concrete sections is introduced. In order to handle the large size of the tables, the concept of multi-database cascade optimization is implemented. The final design has to comply with the provisions of European design codes. The proposed methodology allows for a significant reduction of the direct construction cost combined with improved control of the seismic performance under earthquake loading.
Keywords: Structural optimization; Reinforced concrete; Evolution strategies; Reliability based optimization; Mean annual frequency; Response history analysis